Measurement-induced nonlocality in the W and Greenberger–Horne–Zeilinger superposition states - 林秦 白彦魁 叶明勇 林秀敏 (Chinese physics B, 2015)
Measurement-induced nonlocality（MIN） is a newly defined quantity to measure correlations in bipartite quantum states [Luo S and Fu S 2011 Phys. Rev. Lett. 106 120401]. MIN in the n-qubit W and Greenberger–Horne–Zeilinger（GHZ） superposition states is considered. It is revealed that n = 3 and n ≥ 4 states have very different characteristics,especially the monogamy relation about MIN, and the monogamy equality of MIN is held in all n-qubit W states（n ≥ 3）.